Foaming of Microcellular PP-MWCNT Nanocomposite in a Sub-Critical CO2 Process. Issue 1 (January 2013) - Dolomanova, Viktoriya; Kumar, Vipin; Pyrz, Ryszard; Madaleno, Liliana A.O.; Jensen, Lars R.; Rauhe, Jens Chr. M.
The present work covers the processing route and investigation of PP-MWCNT nanocomposite foams. CO2 is used as a blowing agent in a batch foaming process with a saturation pressure range of 3-7 MPa. Carbon nanotubes act as nucleating agents during the foaming process, which is supported by SEM image analysis and DSC study. Relative density measurements have demonstrated that even though MWCNT promote nucleation of a large amount of cells, the densities of PP-MWCNT nanocomposite foams do not differ significantly from pure PP samples.